Subuh Mubarokah in Formation of Academic Culture at University - Rosalina, Linda; Dewi, Muharika; Ikhlas, Al; Yuliana, Yuliana; Faridah, Anni; Hamzah, Prima Kurniati (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
Academic Culture is the habituation that can characterize an institution in college; good quality culture ensures the development of proper academic services. Technology advancement that threatens morality and academic culture must be anticipated with spiritually nuanced programs like the Subuh Mubarokahh program. As with any program, evaluation must be carried out. This research aims to evaluate behavior change and the benefits of academic culture activities. This is descriptive quantitative non-associative research, with a questionnaire as the instrument; participants included 43 lecturers and 504 students from Padang State University's Faculty of Tourism and Hospitality. According to the research results, the benefits of improving personal qualities that encourage the quality of faith and pious deeds as a Muslim are very high, and the development of a quality academic culture of kriya, ruhiyah, and badaniyah from personal lecturers and students. The program evaluation recommends that the Subuh mubarokah always be carried out by developing studies that align with the needs of lecturers and students to ensure the program's benefits in the realization of an academic culture that becomes the self-image of a quality institution.